On-site reactor for treating source-separated human urine with sparingly soluble fumaric acid in building-scale sanitation systems - Simha, Prithvi; Ahopalo, Nea; Pay, Oliver; Jermakka, Johannes; Vasiljev, Anastasija (Frontiers in Environmental Science, 2025)
To complement innovations at the front- and back-ends of source-separating sanitation systems, this study demonstrates a novel approach for stabilising human urine using sparingly soluble fumaric acid. A reactor was developed to dose fumaric acid passively into freshly excreted urine and was operated to mimic more than 250 typical urination events over 15 days. Fumaric acid at a dose of 5.6 g L-1 effectively maintained urine pH below 4.0, inhibiting enzymatic urea hydrolysis and preventing the precipitation of alkaline earth metals and phosphates, thereby protecting downstream infrastructure from blockages. The stabilised urine retained all its constituents, except for 20% of the sulphate. Novel UV-Vis monitoring techniques were introduced to track fumaric acid depletion (ΔAbs221) and solids settling rate (ΔAbs660), and were demonstrated to be practical surrogates for assessing real-time reactor performance. With an estimated operating cost of less than US$ 5 per person per year, this reactor provides a simple, cost-effective, and scalable solution for stabilising urine in decentralised settings.